Patterns of recurrence after resection of gallbladder cancer without routine extrahepatic bile duct resection. Issue 7 (7th November 2013) - Wiggers, Jimme K.; Groot Koerkamp, Bas; Ovadia, Zachri; Busch, Olivier R. C.; Gouma, Dirk J.; van Gulik, Thomas M.
Abstract Objective Routine extrahepatic bile duct (EBD) resection in non‐jaundiced patients with gallbladder cancer (GBC) is controversial. The aim of this study was to retrospectively analyse patterns of recurrence in patients who underwent resection of GBC without routine EBD resection. Methods This analysis referred to 58 patients who had undergone explorative laparotomy for GBC during 2000–2012 at a single, tertiary referral centre. Overall survival, time to recurrence, and patterns of recurrence were assessed in patients who underwent conventional negative‐margin (R0) resection without routine EBD resection. Results Of 58 patients submitted to explorative laparotomy for GBC, 26 (45%) patients underwent R0 resection without EBD resection (tumour stage T1b in five patients, T2 in 17, T3 in three, and T4 in one). The 3‐year survival rate among these patients was 78% at a median follow‐up of 33 months (range: 13–127 months). Seven patients developed recurrent disease at a median of 9 months (range: 2–25 months) after resection. No patients developed isolated recurrent disease at the EBD. Conclusions Of 26 patients resected for GBC, none developed isolated recurrent disease at the EBD after conventional resection of GBC without EBD resection. This finding suggests that routine EBD resection is of no additional value.